Examining the Relationship between Customer Experience and Customer Equity in South Asia’s Health Sector - Farhana, Nadia; Abdul Mohsin, Ainul Mohsein; Kamalul Ariffin, Shaizatulaqma (Journal of Entrepreneurship, Business and Economics; Vol 9 No 1 (2021), 2021)
This study aims to examine the relationship between customer experience and customer equity in pre-selected private hospitals in Bangladesh. In specific, this study intends to examine the relationship between customer sensory experience, affective experience, behavioural experience and intellectual experience toward customer equity dimension (value equity, brand equity, relationship equity). Bangladesh aspires to develop its healthcare industry to meet its vast population needs. Considering the significance of customer experience and customer equity to the sustainability of the healthcare industry, this study analysed the relationships of these two constructs and examined the authenticity of the Equity Theory and the Social Exchange Theory that underpinned them. This study adopted a cross-sectional research design and distributed 500 survey questionnaires, off 500, 260 samples are acceptable for further analysis using SmartPLS. The findings revealed that customer sensory experience, affective experience, behavioural experience, and intellectual experience positively impact the customer equity dimension, namely, value equity, brand equity, and relationship equity. Furthermore, this study reveals that experiential marketing has an impact on building strong customer equity for the service organisation. This research contributes to the literature on customer experience by examining its relationship with consumer equity among respondent in private hospitals. This study has integrated Equity Theory and Social Exchange Theory to support the framework model. These findings offer empirical evidence that patients are likely to reciprocate if treated equitably by engaging in behaviours that enhance the relationship between hospital and patient. Research paper Keywords: Customer Experience; Customer Equity; Equity Theory; Healthcare Industry; Social Exchange Theory Reference to this paper should be made as follows: Farhana, N., Abdul Mohsin, A. M., & Kamalul Ariffin S. (2021). Examining the Relationship between Customer Experience and Customer Equity in South Asia’s Health Sector. Journal of Entrepreneurship, Business and Economics , 9 (1), 275–301.